IMPACT OF POLYPROPYLENE MACRO FIBER ON MECHANICAL AND BOND STRENGTH IN SUPER-SULPHATED CEMENT CONCRETE - Lucky Manuel; Herry Suryadi Djayaprabha (Program Studi Teknik Sipil, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2026)
Super-sulphated cement concrete (SSC) has emerged as a promising low carbon binder system due to its high ground granulated blast furnace slag (GGBFS) content, however,par its mechanical performance is often limited by internal expansion, slow early hydration, and vulnerability to microcracking. Polypropylene macro fibers (PMF) have the potential to overcome these issues, but their influence on SSC particularly sulphate-activated systems has not been widely established. This study investigates the effects of PMF incorporation (0–1% by volume) on the mechanical performance, bond behavior, and microstructure of SSC activated using Sodium sulphate (Na₂SO₄) as sulfate activator and OPC as alkali activator. Compressive, flexural, and bond strength tests were conducted alongside ultrasonic pulse velocity (UPV) evaluations and microstructural analysis using XRD and SEM. The results demonstrate that PMF addition significantly enhances SSC performance. At 1% fiber content, compressive, flexural, and bond strengths improved by 20.41%, 55.31%, and 62.05%, respectively, compared with fiber-free SSC, accompanied by higher UPV values indicating a denser matrix. Microstructural observations confirmed the formation of C–S–H, ettringite, and portlandite, with improved matrix integrity in fibrous mixtures. These findings highlight the effectiveness of PMF in improving the structural performance and durability indicators of sulphate-activated slag concrete, offering practical insights for developing sustainable and fiber reinforced low carbon construction materials.